FORENSIC ACCOUNTING AND INCREASING THE QUALITY OF EXTERNAL AUDIT - Lecturar. Ahmed Mohsen Hassan Shammari (Scholars Digest Publishing, 2023)
The present research aims to indicate the extent of the contribution that forensic accounting has towards the work of auditing companies and offices in Iraq from two aspects. The first aspect is focused on combating fraud and manipulation carried out by companies in their financial statements, and the second aspect, on facing lawsuits filed against auditors in courts. In order to achieve these goals, the research is based on preparing a questionnaire and then distributing it to the research sample using the arithmetic mean and standard deviation to analyse the results of the questionnaire based on the 5-point Likert-Type scale to reach the results and test the research hypotheses. The most important conclusion of the research is that forensic accounting has a role in identifying corruption cases and discovering cases of fraud within the economic units, and that it also contributes to strengthening the position of the auditors in the case brought against them in court. Moreover, the research delivered a set of recommendations, including the need for auditing companies and offices to appoint a person familiar with and qualified in forensic accounting, who is able to help in identifying corruption cases and discovering cases of fraud in the economic units that are audited, and also enhances the position of the auditors in court on the lawsuits filed against them.